Synthesis, Pharmacological Evaluation and Hydrolytic Behaviour of Ethylenediamine and Benzathine Conjugates of Naproxen: Diamide Derivatives as Potential Prodrugs - CHATTERJEE, N.R.; THUBE, S.S.; KULKARNI, A.A.; CHANDAK, B.G.; DESHPANDE, A.D. (Asian Journal of Chemistry, 2010)
The carboxylic acid group of naproxen was masked by synthesizing its diamide conjugates with ethylenediamine and benzathine (4a and 4b) by carbodiimide assisted coupling method. In vitro hydrolysis of conjugates showed that they were stable in HCl buffer (pH 1.2) indicating that the conjugates did not break in stomach and therefore naproxen did not release at gastric pH; whereas in phosphate buffer (pH 7.4) significant hydrolysis following first order kinetics was observed releasing naproxen in adequate amount. The synthesized compounds 4a and 4b retained antiinflammatory activity intact and exhibited better analgesic activity along with much reduced ulcerogenicity on comparison with the parent drug. These findings suggested that both the conjugates are better in action and possessed less gastrointestinal side effects compared to the parent drug. However, 4b showed better analgesic activity and longer action (t1/2) than 4a and hence it could be considered as a more suitable candidate to act as prodrug among the two.